Felty’s syndrome and T-cell large granular lymphocyte leukaemia – similarities and differences - Prochorec-Sobieszek, Monika; Wagner, Teresa; Maryniak, Renata K. (Reumatologia/Rheumatology, 2007)
Recent studies suggest that Felty’s syndrome (FS) and T-cell large granular lymphocyte leukaemia (T-LGL) are related disorders that appear to share some pathogenetic mechanisms and clinical features: T-cell large granular lymphocytosis, immune-mediated neutrophil destruction resulting in neutropenia, variable splenomegaly and arthritis. FS is characterized by severe articular and extra-articular manifestations of rheumatoid arthritis (RA), neutropenia and splenomegaly, and in 30% of patients FS is associated with T-cell large granular lymphocytosis. On the other hand, T-LGL presents with monoclonal infiltration of T large granular lymphocytes in the bone marrow and spleen, neutropenia and splenomegaly, and in 25-35% patients it is associated with RA. The article reviews pathogenetic, histopathological, immunogenetic and clinical relations between these two diseases.